Nursing Intervention For Mother With Postpartum Fatigue : A Literature Review - Edita Pusparatri; Sari Sudarmiati; Sri Rejeki (Universitas Muhammadiyah Semarang, 2022)
Postpartum fatigue is a common and natural phenomenon that often affects mothers after giving birth. This phenomenon occurs immediately after delivery and reaches the highest level of fatigue in the first 24 hours, so non-pharmacological nursing interventions are very effective when focused from the beginning of the postpartum period to reduce the level of postpartum fatigue. This literature aims to determine effective nursing interventions used to reduce postpartum maternal fatigue. The method used in this literature review begins with determining the topic, then determining keywords to search for journals. Scopus, ScienceDirect and PubMed are the databases used, searching for journals from 2010 to 2018 consisting of several research articles. The results of the synthesis of articles that have been explored show that nursing interventions with non-pharmacological methods can be applied to reduce fatigue in postpartum mothers, this is because non-pharmacological methods are easier, cheaper, acceptable to patients, non-invasive and without side effects. An effective nursing intervention to reduce postpartum fatigue is to choose one of the methods including slow stroke back massage, meridian acupressure and pilates exercises.